2019
DOI: 10.1111/pce.13614
|View full text |Cite
|
Sign up to set email alerts
|

TaCER1‐1A is involved in cuticular wax alkane biosynthesis in hexaploid wheat and responds to plant abiotic stresses

Abstract: To protect above‐ground plant organs from excessive water loss, their surfaces are coated by waxes. The genes involved in wax formation have been investigated in detail in Arabidopsis but scarcely in crop species. Here, we aimed to isolate and characterize a CER1 enzyme responsible for formation of the very long‐chain alkanes present in high concentrations especially during late stages of wheat development. On the basis of comparative wax and transcriptome analyses of various wheat organs, we selected TaCER1‐1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 64 publications
5
25
0
1
Order By: Relevance
“…We found that CsCER1-LIKE2 and CsCER3-LIKE1 expressions increased with ripening in both genotypes, but remained at lower levels in the Pinalate (Figure 7). This agrees with the ABA-activated induction of CER1 and the consequent increase in alkane production in wheat leaves (Li et al, 2019). Our gene expression results are consistent with the lower content of aldehydes in the Pinalate than in the Navelate in FC fruit ( Figure 3B), and also with the reduction in n-alkanes from stage Bk to the end of ripening in the mutant, which supports a role for ABA in the regulation of these fractions ( Supplementary Table S5).…”
Section: Abscisic Acid Deficiency Causes Changes In Cuticle-related Gsupporting
confidence: 88%
“…We found that CsCER1-LIKE2 and CsCER3-LIKE1 expressions increased with ripening in both genotypes, but remained at lower levels in the Pinalate (Figure 7). This agrees with the ABA-activated induction of CER1 and the consequent increase in alkane production in wheat leaves (Li et al, 2019). Our gene expression results are consistent with the lower content of aldehydes in the Pinalate than in the Navelate in FC fruit ( Figure 3B), and also with the reduction in n-alkanes from stage Bk to the end of ripening in the mutant, which supports a role for ABA in the regulation of these fractions ( Supplementary Table S5).…”
Section: Abscisic Acid Deficiency Causes Changes In Cuticle-related Gsupporting
confidence: 88%
“…ZmGL1 in Zea and OsWSL2 in Oryza share 62% and 64.46% protein identity with AtCER3, respectively. Although cer1-4 was not as sensitive as cer3-6 in our studies, recently, the ortholog of CER1 in wheat, TaCER1-1A, was reported to have significantly reduced levels of C33 alkanes in wheat, while overexpression in rice resulted in elevated levels of C25-C33 alkanes compared to the wild type [62]. We provide further evidence that the role of the CER3 protein can be extended beyond dehydration stress, with a role in frost avoidance.…”
Section: Discussionsupporting
confidence: 41%
“…It is common to observe low g min values in desert-adapted plant species 56 . In fact, Bolger et al 13 observed three times more cuticular wax in S. pennellii plants than in S. lycopersicum plants, which consists mainly of long-chain alkanes, molecules that were previously suggested as responsible for increasing cuticle resistance to water flow [57][58][59] . Therefore, we expected lower g min for LA 716 compared to M82, especially in the stress treatment, which did not happen here.…”
Section: Discussionmentioning
confidence: 99%